Conditional duel, as methodical reception of perfection to technical tactical preparedness in kickboxing, and its classification - O.S. Skyrta (Physical Education of Students, 2013)
A place and role of conditional duels is certain in the system of training in kickboxing as a methodical reception of perfection to technical tactical preparedness of sportsmen. The analysis is conducted on 24 literary sources. The alternative variant of classification of conditional duels is offered, in which for basis of distributing limitation of volume is chosen battle technical tactical actions and them sets. It is suggested to group conditional duels for duels with one-sided a task and multilateral tasks. Also for duels with the narrowly limited actions of partners and duels with wide technical tactical by tasks. The use of alternative classification is given by possibility. It is recommended to utillize in training narrow limitation of actions of one of partners and considerable expansion technical tactical tasks other. Offered to recommendation on artificial limitation of battle facilities in conditional duels and forming of individual manner of embay.